Spatial distribution analysis of the Lower Magdalenian human burial in El Mirón Cave (Cantabria, Spain). (August 2015) - Geiling, Jeanne Marie; Marín-Arroyo, Ana B.
Abstract: By using Geographical Information System software this study presents the spatial distribution of the human remains and features within the burial found in a Lower Magdalenian level of El Mirón cave (Cantabria, Spain). The aim is to identify how the interment was created and discern its primary or secondary origin. Three-dimensional analyses have been applied to recognize the physical location of the burial and its structural elements in relation with the grave assemblage and the significance of the red ochre and specular hematite in the burial context. In addition, a comparison of the vertical and horizontal dispersal of human skeletal elements was carried out according to their representation and evidence of taphonomic modifications. The association of human bones with other archaeological finds was also taken into account. The results show that the human body was placed at the edge of the living area of the site, at the rear of the cave vestibule, but in a separate place behind an engraved block and covered with limestone rocks. The position of the anatomical elements and the spatial distribution of the taphonomic bone modifications prove that it was a primary burial, minimally disturbed by carnivores, after body decomposition. The absence of the cranium and most of the long bones seems to be the result of a deliberate anthropogenic extraction from the burial pit, possibly for redeposition at another, unknown location perhaps a secondary burial. This fact disturbed the initial primary body deposition. Therefore, the results show that the El Mirón Lower Magdalenian burial was a disturbed primary interment, rather than a secondary deposit. Highlights: GIS analysis is used as a tool to study a Lower Magdalenian human burial. A separate place, behind an engraved block, was prepared to deposit the body. An adult woman lying on her left side, in a body flexed position was reconstructed. Red ochre were deliberately placed covering the human bones. Distortion of the original interment is inferred.